Fiscal policy and private investment in selected West African countries - Joseph A. Omojolaibi; Tochi-Nze P. Okenesi; Ekundayo P. Mesagan (CBN Journal of Applied Statistics, 2016)
This study sets out to examine the nexus between fiscal policy and private investment in five selected West African countries using annual data from 1993 to 2014. Employing Fixed Effect Model for Panel data ordinary least square approach, the results showed the existence of a significant crowding in effect of government capital expenditure and tax revenue while non-tax revenue showed a crowding out effect. Recurrent expenditure and external debt also showed crowding out effects but these were insignificant. The accelerator effect of output growth was also found to be insignificant across the countries over the time period. The study called for concerted efforts from these countries to channel funds towards capital projects and also restructure the tax systems to prevent the negative effects of public debt on private investment.
Keywords: H3; E2; E65; 330; Fiscal Policy; Private Investment; West African Countries; Public Debt; Growth